Clinical evaluation of three‐dimensional late enhancement MRI. Issue 6 (1st November 2016) - Bratis, Konstantinos; Henningsson, Markus; Grigoratos, Chrisanthos; Omodarme, Matteo Dell'; Chasapides, Konstantinos; Botnar, Rene; Nagel, Eike
Abstract : Purpose: To assess the diagnostic value of three‐dimensional late enhancement (3D‐LGE) for the detection of myocardial necrosis in a routine clinical setting. 3D‐LGE has been proposed as a novel magnetic resonance (MR) technique for the accurate detection of myocardial scar in both the ventricles and atria. Its performance in clinical practice has been poorly examined. Materials and Methods: Fifty‐seven patients referred for cardiac MR examination including scar imaging were prospectively enrolled. Gadolinium enhanced single breathhold 3D T1‐weighted gradient‐echo inversion recovery sequence and a conventional 2D‐LGE sequence were performed using a 1.5 Tesla clinical MR imaging system. The presence, pattern and transmurality of LGE, diagnostic accuracy and level of diagnostic confidence as well as image quality (median quality, mean LGE signal intensity, sharpness, virtual scan time) were graded on a 4‐point scale. Results: Interpretable images were obtained in 52/57 2D‐LGE and in 47/57 3D high‐resolution exams. LGE was detected in 10 patients with ischemic pattern, 9 with nonischemic pattern, while it was absent in 28, resulting in a total of 47 complete datasets. The detection of global and segmental LGE as well as its transmural extent were similar for both techniques ( P  = 0.65, P  = 0.305, and P  = 0.15, respectively). Image quality (median quality, LGE/ myocardial and LGE/ blood pool sharpness) was similar for both techniques ( P  = 0.740, P  = 0.34, and P  = 1.00, respectively), but LGE signal intensity was higher with 2D ( P  = 0.020). Conclusion: 3D‐LGE diagnostic and quality scores were comparable to 2D‐LGE in a routine clinical setting. Further technical refinement is required for 3D LGE to offer a reliable alternative for high quality scar imaging. Level of Evidence : 2 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;45:1675–1683